2019
DOI: 10.1021/acssuschemeng.8b05513
|View full text |Cite
|
Sign up to set email alerts
|

Pyrohydrolysis of CaCl2 Waste for the Recovery of HCl Acid upon the Synergistic Effects from MgCl2 and Silica

Abstract: In this paper, an efficient HCl acid recovery method from the mixture of alkaline-earth-metal chlorides waste was demonstrated via co-pyrohydrolysis in a laboratory-scale horizontal furnace in a temperature range of 700−1000 °C, and fixed additions of SiO 2 and steam. The synergistic effect of MgCl 2 on the HCl recovery from CaCl 2 was explored intensively. A double-sided effect was revealed. For the reaction temperatures below 1000 °C, the MgCl 2 addition delayed the HCl release through competing with CaCl 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The use of MgCl 2 was merely to ease the collection of the reaction residue, which would otherwise melt and stick firmly on the corundum boat at high temperatures. Compared to CaCl 2 • 4H 2 O, MgCl 2 • 6H 2 O decomposed quickly into MgO below 500°C, [11] which then served as an inert substance to dilute the CaCl 2 melt. Additionally, to rule out any effect of MgCl 2 addition, its amount was varied purposely from 1 to 4 moles per mole of CaCl 2 .…”
Section: Experimental Section Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of MgCl 2 was merely to ease the collection of the reaction residue, which would otherwise melt and stick firmly on the corundum boat at high temperatures. Compared to CaCl 2 • 4H 2 O, MgCl 2 • 6H 2 O decomposed quickly into MgO below 500°C, [11] which then served as an inert substance to dilute the CaCl 2 melt. Additionally, to rule out any effect of MgCl 2 addition, its amount was varied purposely from 1 to 4 moles per mole of CaCl 2 .…”
Section: Experimental Section Experimental Methodsmentioning
confidence: 99%
“…An open system in the FactSage was used to simulate the continuous flow of the gas. [11] Ca(OH)Cl was synthesized as follows. Around 10 g of CaCl 2 • 4H 2 O and CaO at a molar ratio of 2 : 1 was added to about 10 mL Milli-Q water and then stirred for around 12 h in a thermostatically controlled water bath at 70°C.…”
Section: Hcl Regeneration Extent Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al 66 revealed a double-sided effect of MgCl 2 on the pyrohydrolysis of CaCl 2 at 700−1000 °C, under a fixed molar ratio of 1 for SiO 2 /CaCl 2 in argon containing 70 vol % steam. In the initial heating stage, the MgCl 2 addition delayed the pyrohydrolysis of CaCl 2 through competing with CaCl 2 for the inclusion into the silica matrix.…”
Section: Energy and Fuelsmentioning
confidence: 99%